PENGARUH GAYA PENGASUHAN DAN TEMAN SEBAYA TERHADAP PERILAKU KONSUMSI ROKOK SISWA SMA DI KOTA BOGOR - Pramintari, Ratna Duhita; Hastuti, Dwi; Djamaludin, Mohammad Djemjem (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2014)
Smoking is risky behavior for adolescence, and there are family, peer, and school that play a role in the formation of adolescent behavior. This research aimed to analyze the influence of parenting style and peer relations with smoking behavior among high school student in Bogor. This research was conducted in six schools and data was collected on May until June 2012. The sampling of this research was 200 adolescents consisted of 100 boys and 100 girls that was selected by random sampling technique. The sample criteria of this research were grade 10 students and came from an intact family. The Result showed , prevalence of adolescent?s smoking behavior was 18.5 percent. There was no relation between parenting style with adolescent?s smoking behavior. Gender was related with adolescent?s smoking behavior. Logistic Regression analyses showed that gender, peer relations, and perception to smoking significantly influenced to smoking behavior. Which means that boys riskier to smoking behavior, and the stronger peer relations and perception toward smoking behavior riskier to their?s smoking behavior